2011
DOI: 10.1016/j.apm.2010.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Formation of uniformly sized metal droplets from a capillary jet by electromagnetic force

Abstract: a b s t r a c tA new method for producing uniformly sized metal droplets is proposed. In this method, an intermittent electromagnetic pinch force is applied to a capillary jet of liquid metal to generate fluctuations of equal interval on the surface of the jet. As the fluctuations grow, the liquid metal jet breaks into small droplets whose size depends on the frequency of the intermittent electromagnetic pinch force. The breakup of the capillary jet is numerically simulated by performing multiphase fluid flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 12 publications
0
4
0
2
Order By: Relevance
“…Notably, the granulation process study in the above articles using the computational fluid dynamics methods makes it possible to determine the influence of technological regimes and the prillers design on the main process parameters. Also, in many studies, it is indicated that the numerical modeling results of processes occurring in prillers and drying towers give a good similarity with the results of the experiments [10][11][12].…”
Section: Literature Reviewmentioning
confidence: 61%
“…Notably, the granulation process study in the above articles using the computational fluid dynamics methods makes it possible to determine the influence of technological regimes and the prillers design on the main process parameters. Also, in many studies, it is indicated that the numerical modeling results of processes occurring in prillers and drying towers give a good similarity with the results of the experiments [10][11][12].…”
Section: Literature Reviewmentioning
confidence: 61%
“…Apart from that, a method of droplet generation based on applying a modulated AC high-frequency magnetic field in the localized region of capillary break-up has been studied by other authors using numerical modeling and experiments. [26,27] It was found that the droplet size can be tailored by the frequency of the intermittent electromagnetic pinch force.…”
Section: A ø40 MM Tantalum Electrodementioning
confidence: 99%
“…For the generation of low melting point droplets (T melt < 427 °C), materials in the liquid phase are used the most frequently. Methods of continuous droplet generation are based on liquid metal stream break up due to induced stream instability which can be caused by low-energy mechanical vibration (Liu and Omre 2001), or by electromagnetic forces (Shimasaki and Taniguchi, 2009). In DoD generation a liquid metal is squeezed out through a nozzle by applying a high energy pulse which can be generated by a piezoelectric actuator (Wehl et al, 2003), a vibration plunger (Sohn and Yang, 2005), or a pneumatic actuator (Cheng et al, 2005).…”
Section: Introductionmentioning
confidence: 99%